A FASHION FLOP: THE INNOVATIVE DESIGN PROTECTION AND PIRACY PREVENTION ACT - Purcell, Lauren E. (Journal of Law and Commerce, 2013)
A FASHION FLOP: THE INNOVATIVE DESIGN PROTECTION AND PIRACY PREVENTION ACT